Introduction To Body Parts Using English Learning Media - Rahayu, Arum Dewi; Harahap, Mutiara Hairani; Nasution, Salsabila Azwita (Yayasan Daarul Huda Kruengmane, 2024)
The existence of the learning media nowadays is more developed in media technology as well as its delivery. Generally, learning media in elementary level is still using conventional method and focus on text only. Because of this condition, it is very important to have alternative media which is more interesting to be used, in this case, a learning media was proposed as the media for introducing parts of body for elementary students. For developing this application, parts of body could be introduced based on learning material in curriculum 2013. It was also developed by using Godfrey method. It can be significantly used for introducing parts of body in English for grade 1-2. It could be very helpful for the teachers or students where they don’t only use lecture method but it can be use as one of alternative media. This 2D learning media was designed by using adobe flash CS6, Action Script 3. Based on the learning media testing, there are 89,41% who agreed that this application for English learning as the introduction for parts of body is easy to be used.